A new model for Islamic cooperative mortgage of housing finance. Issue 4 (4th April 2019) - Nasir, Aslina; Abdullah, Lazim
Abstract : Purpose: This study aims to propose a new model of Islamic cooperative mortgage of housing finance (ICOM) to provide a lower monthly initial amount with a longer tenure for the low- and middle-income members. This model is developed to ease the burden on borrowers concerning the high initial down payment (ID). Design/methodology/approach: The ICOM model is a no-interest mortgage and is developed based on the cooperative home mortgage model by Ebrahim (2009). The model is verified using numerical examples to ensure its feasibility to produce lower monthly initial amounts and compared to the cooperative home mortgage. Findings: From the numerical example, the ICOM model shows a lower monthly initial amount with a longer tenure compared to the cooperative home mortgage. The monthly payment is also lower than the cooperative home mortgage. Research limitations/implications: The authors compare their model with Ebrahim's (2009) cooperative home mortgage because of a constraint of limited previous studies on housing finance. Therefore, this model is developed by considering the unaffordability of the initial down payment among low-income borrowers. As this model introduces a lower monthly initial amount, the authors expect it can reduce the unaffordability problem of high initial down payment. Practical implications: The authors also expect that a lower monthly initial amount with a longer tenure can ease the burden among the low-income borrowers by reducing their consumption on housing. Originality/value: This paper provides a non-interest Islamic cooperative mortgage and lower monthly initial amount with a longer tenure for the low- and middle-income borrowers.